EVALUASI KINERJA SISTEM PENDINGIN KOMPRESI UAP VRF DENGAN SIKLUS INJEKSI - Rachman, Arfidian; Yuana Dewi, Arfita; Effendi, Asnal; Nesti, Lisa (ITP Press, 2023)
As a result of a decrease in the mass flow rate at the inlet section of a variable refrigerant flow (VRF) cooling system, the refrigerant flow system performs poorly. To increase efficiency the steam injection cycle method is used. The effects of steam injection are theoretically explored in this study over a wide range of medium pressures and ambient temperatures, and the findings are supported by experimental data. Compressor heating capacity, input power, coefficient of performance (COP), and isentropic efficiency are all affected by pressure. At low ambient temperatures, the increase in COP by steam injection is remarkable. In this study, the performance of the cooling system with the injection cycle was evaluated, the system with this injection cycle resulted in an increase in cooling capacity of 3.26% and an energy efficiency ratio (EER) of 2.32%.